Structural performance of composite connections with a uniaxial symmetric steel-beam section. (15th January 2023) - Xu, Ying-lu; Su, Yao-xuan; Shang, Yong-fang; Liu, Zi-long; Tian, Li-min
Highlights: Two novel design strategies for composite connections were proposed. Three half-scale composite connection specimens were tested. Nonlinear finite-element modeling of the composite connection was performed. Design parameters for practical design applications were recommended. Abstract: To reduce the negative effects of composite action, this study proposes two novel design strategies for composite connections with a uniaxial symmetric steel-beam section. This work experimentally and numerically elucidates the behavior of composite connections proposed by widening or reducing beam bottom flanges. Cyclic testing of three half-scale specimens is conducted to verify the proposed connection details. Detailed test observations and results are reported. Cyclic curves and strain development at key positions are experimentally obtained. Results show that a composite connection with only widened beam bottom flanges performs considerably better than that with only reduced beam bottom flanges. Nonlinear finite-element modeling of the composite connection with only widened beam bottom flanges is performed as a supplement to the experimental study. Results show that good workmanship and sound welding quality are required to provide a reliable composite connection. The concrete slab slightly affects the neutral axis of the composite beam under negative bending, while the neutral axis shifts significantly toward the beam top flange under positive bending. The proposed composite connection with only widened beam bottom flanges can effectively move the plastic hinge away from the column face and thus achieve more reliable structural characteristics. Based on the parametric study and experimental results, the design parameters for practical design applications were recommended.